Three Center of Education on A Vocational Learning Approach Based on Local Wisdom in Special Schools in Bali Province - Ayomsari, Silvia Widi; Azizah, Nur (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
An ideal vocational learning program should be designed considering the learners' residential environment. This research focuses on implementing the Three Centers of Education concept in vocational learning based on local wisdom in Special Schools in Bali Province. The study employed a descriptive research method with a qualitative approach and was conducted through interviews with eight informants from two Special Schools in Bali Province. The findings illustrate that vocational skills learning based on local wisdom, specifically in weaving Endek fabric and coconut shell crafts in Bali, involves various stakeholders, including schools, parents, and the community. This skills-based learning imparts practical skills and reflects local wisdom and the school's commitment to preserving it. Furthermore, efforts to ensure program sustainability, introduce innovation, and enhance the quality of learning signify the school's long-term perspective in continuing to impact the future lives of the learners positively.